Benefits of natural childbirth for mothers and newborns: A literature review (Research, Society and Development, 2024)
Objective: This study aimed to review the literature on the benefits of natural childbirth and the risks associated with cesarean delivery, focusing on promoting safer and more humanized obstetric practices. Materials and Methods: The research was conducted as na review, covering articles published between 2009 and 2024 in databases such as PubMed, SciELO, and LILACS. The inclusion criteria involved studies addressing maternal and neonatal outcomes, obstetric practices, and cultural perceptions related to childbirth. Results: The results highlight that natural childbirth offers significant advantages for both mother and baby, including lower infection rates, faster recovery, reduced need for medical interventions, and better neonatal adaptation. In contrast, although cesarean delivery is a safe alternative in specific cases, it is associated with higher risks of maternal and neonatal complications, such as hemorrhage, infections, and respiratory difficulties for the newborn. The review also revealed a scenario of excessive medicalization and cultural influences favoring cesarean sections, often without proper clinical indication. Conclusion: It is concluded that it is essential to promote public policies and evidence-based obstetric practices that prioritize natural childbirth when it is safe and desired by the woman. It is recommended that healthcare professionals adopt a patient-centered approach, providing clear information on the risks and benefits of each type of delivery and respecting women's informed choices.